Power electronics for renewable energy sources - Nayar, Chemmangot; Islam, Syed; Dehbonei, H.; Tan, K.; Sharma, H. (Elsevier Inc., 2011)
This chapter focuses on solar photovoltaic and wind power. Stand-alone PV energy system requires storage to meet the energy demand during periods of low solar irradiation and nighttime. Blocking diodes in series with PV modules are used to prevent the batteries from being discharged through the PV cells at night when there is no sun available to generate energy. Two of the main factors that have been identified as limiting criteria for the cycle life of batteries in PV power systems are incomplete charging and prolonged operation at a low state-of-charge (SOC). The power output of the PV array is sampled at an every definite sampling period and compared with the previous value. Voltage source inverters are usually used in stand-alone applications. They can be single phase or three phase. There are three switching techniques commonly used: square wave, quasi-square wave, and pulse width modulation. Centrifugal pumps are used for low-head applications especially if they are directly interfaced with the solar panels. Centrifugal pumps are designed for fixed-head applications and the pressure difference generated increases in relation to the speed of pump.